2002
DOI: 10.1093/nar/gkf673
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cellular mRNA targets for RNA-binding protein Sam68

Abstract: Sam68 (Src-associated in mitosis, 68 kDa), a nuclear RNA-binding protein, has been postulated to play a role in cell-growth control as a modulator of signal transduction and activation of RNA metabolism. Although Sam68 was demonstrated to bind to the UAAA sequences in synthetic oligoribonucleotides and poly(U) homopolymers in vitro, the legitimate cellular mRNA target remained unclear. By using the differential display and cDNA-representational difference analysis techniques, followed by reverse transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 44 publications
5
56
0
1
Order By: Relevance
“…In agreement with experimental evidence (Itoh et al 2002;Sellier et al 2010), we predict that SAM68 does not interact with CGG repeats (Fig. 3A) or negative controls β-actin 1291-1417 nt ( Fig.…”
Section: Protein Sequestration In Cgg Aggregatessupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with experimental evidence (Itoh et al 2002;Sellier et al 2010), we predict that SAM68 does not interact with CGG repeats (Fig. 3A) or negative controls β-actin 1291-1417 nt ( Fig.…”
Section: Protein Sequestration In Cgg Aggregatessupporting
confidence: 91%
“…3C) and hnRNPA2/B1 region 435-1173 nt ( Fig. 3E; Supplemental Table 1), as reported in previous studies (Itoh et al 2002;Sellier et al 2010). The fact that SAM68 does not interact with CGG repeats suggests that other proteins could be involved in its sequestration.…”
Section: Protein Sequestration In Cgg Aggregatessupporting
confidence: 81%
“…The mRNA of heterogenous nuclear ribonucleoprotein A1 (hnRNP A1), a negative control, did not associate with HuR. 31 By scanning the 3 0 -UTR of caspase-9 mRNA, we identified two AREs (ARE1: 1841-1870; ARE2: 1944ARE2: -1988 (Supplementary Figure 2). Gel-shift experiments using radioactive-labeled probes showed that both AREs associate with GST-HuR but not GST alone ( Figure 1E).…”
Section: Resultsmentioning
confidence: 99%
“…It is involved in a variety of pathways, including insulin and T-cell receptor signaling (4), and plays a key role in cell cycle regulation (5). Sam68 exhibits binding specificity for homopolymeric poly(U) RNA and has been shown to recognize UAAA or UUUA sequences with high affinity as determined by Systematic Evolution of Ligands by EXponential Enrichment (SELEX) and in vivo crosslinking (6,7). Post-translational modifications can regulate Sam68 function by critically affecting the accessibility to RNA (8,9).…”
mentioning
confidence: 99%